Activity profile of top-class association football referees in relation to performance in selected physical tests - Mallo, J.; Navarro, E.; Garcia-Aranda, J. M.; Gilis, B.; Helsen, W. F. (Journal of Sports Sciences, 2007)
The aims of the present study were (1) to analyse the physical demands of top-class referees and (2) to compare their official FIFA fitness test results with physical performance during a match. The work rate profiles of 11 international referees were assessed during 12 competitive matches at the 2003 FIFA Under-17 World Cup and then analysed using a bi-dimensional photogrammetric video analysis system based on direct lineal transformation (DLT) algorithms. In the first 15 min of matches, the referees were more active, performing more high-intensity exercise (P < 0.01) than in the first 15 min of the second half. During the second half of matches, the referees covered a shorter distance (P < 0.01), spent more time standing still (P < 0.05), and covered less ground cruising (P < 0.05), sprinting (P < 0.05), and moving backwards (P < 0.001) than in the first half. Also in the second 45 min, the distance of referees from infringements increased (P < 0.05) in the left attacking zone of the filed. There was also a decrease (P < 0.05) in performance in the period following the most high-intensity activity, compared with the mean for the 90 min. Time spent performing high-intensity activities during a match was not related to performance in the 12-min run (r2 = 0.30; P < 0.05), the 200-m sprint (r2 = 0.05; P < 0.05), or the 50-m sprint (r2 = 0.001; P < 0.05). The results of this study show that: (1) top-class referees experienced fatigue at different stages of the match, and (2) the typical field tests used by FIFA (two 50-m and 200-m sprints, followed by a 12-min run) are not correlated with match activities.